Theoretical and Experimental Study on Machining Rectangular Microgroove of Diamond by Femtosecond Laser. Issue 208 (12th June 2020) - Dou, Jian; Cui, Jianlei; Fang, Xuyang; Dong, Xiangyang; Ullah, Naveed; Xu, Muxun
Abstract: The liquid-solid conjugate heat transfer in three-dimensional diamond microgrooves with different cross-section shapes was numerical analyzed by COMSOL, and the results show that rectangular microgrooves have better heat transfer characteristics than triangular and trapezoidal microgrooves. The laser processing experiments of CVD diamond were carried out by using 1030 nm wavelength high repetition frequency femtosecond laser processing system equipped with 2D scanning galvanometer and XYZ stage. By studying the influence of laser power, scanning speed, repeated scanning times and defocusing distance on the size of the microgroove, the appropriate process parameters were obtained. On this basis, the spiral path scanning process with different intervals was designed to adjust the laser intensity absorbed by the side wall and the middle of the microgroove. The diamond microgrooves with nearly rectangular cross section can be machined by using the improved process. This paper provides theoretical and experimental basis for the design and fabrication of diamond microgrooves.